Analisis Yuridis Praktik Top Up Game Online Anak di Bawah Umur Perspektif Maqāṣid al-Syarī‘ah - Naipospos, M Ikhsan H; Hidayat, Rahmat (AL-SULTHANIYAH, 2026)
The rapid growth of the online gaming industry has led to an increasing practice of online game top-ups, including those conducted by minors. This phenomenon raises legal concerns, as minors lack full legal capacity to perform binding legal acts, yet they are actively involved in digital transactions. This study aims to analyze the practice of online game top-ups by minors from the perspectives of positive law and maqāṣid al-sharī‘ah. This research employs a normative-empirical legal method with a qualitative approach, using literature review and interviews as data collection techniques. The findings indicate that online game top-ups conducted by minors potentially involve legal defects due to the absence of legal capacity and weak age verification mechanisms on gaming platforms. From the perspective of maqāṣid al-sharī‘ah, such practices tend to conflict with the objectives of protecting wealth (ḥifẓ al-māl) and intellect (ḥifẓ al-‘aql), as they may encourage consumptive behavior and dependency among minors. This study emphasizes the need to integrate positive law and maqāṣid al-sharī‘ah to strengthen child protection in digital transactions.